Analysis of the mitochondrial genome of Neuroctenus hainanensis and the phylogenetic position of Aradoidea - Yanrui Li; Liangpeng Ji; Xiaoshuan Bai (Scientific Reports)
Abstract In order to understand the mitochondrial genome characteristics of Neuroctenus hainanensis, this study utilized second-generation sequencing technology for sequencing, assembling, and annotating. The N. hainanensis mitochondrial genome is 15,213 bp in length, containing 37 genes and an AT-rich region (817 bp), with the whole genome exhibiting AT bias. Secondary structure analysis of tRNA genes revealed that trnS1 lacks the DHU arm, forming a simple loop structure, while other tRNAs exhibit complete cloverleaf structures. Phylogenetic relationships within Aradidae and the position of Aradoidea within Pentatomomorpha were reconstructed using BI and ML methods. Two species from Cimicomorpha were selected as the outgroup, and 51 species from five superfamilies of Pentatomomorpha were included as the ingroup. Analyses employed PCG12, PCG123, and AA datasets, reconstructed consistent topologies: (Aradoidea + (Pentatomoidea + (Lygaeoidea + (Coreoidea + Pyrrhocoroidea))). Phylogenetic results strongly support N. hainanensis as a member of Neuroctenus and confirm the sister relationship between Neuroctenus and Mezira. This study provides foundational data for analyzing evolutionary relationships within Aradidae.